Pelatihan Pembuatan Surat melalui Mail Merge di Dayah Misbahul Huda - Jamali; Muhammad Jamil (BA: Jurnal Pengabdian kepada Masyarakat, 2024)
The Mail Merge Letter Writing Training at Dayah Misbahul Huda aimed to enhance the administrative staff’s ability to manage correspondence efficiently and professionally using the Mail Merge feature in Microsoft Word. The training was conducted through a combination of lectures, demonstrations, hands-on practice, discussions, and evaluations. The results showed a significant improvement in participants' understanding and technical skills related to automated letter generation based on data sources. The training led to greater efficiency and accuracy in administrative tasks, reducing errors commonly found in manual processes. It also contributed to increased professionalism in correspondence management and opened opportunities for further development in digitalizing administrative processes. It is recommended that similar training be conducted regularly to support the digital transformation within Islamic boarding schools (pesantren).